Deep-Sequencing Identification of MicroRNA Biomarkers in Serum Exosomes for Early Pig Pregnancy - Zhou, Chen; Cai, Gengyuan; Meng, Fanming; Xu, Zhiqian; He, Yanjuan; Hu, Qun; Zheng, Enqin; Huang, Sixiu; Xu, Zheng; Gu, Ting; Hu, Bin; Wu, Zhenfang; et al. (Frontiers in Genetics, 2020)
Early pregnancy diagnosis in sows can significantly improve the efficiency of pig industry. Exosomes are membrane-covered nanovesicles that can transport microRNAs (miRNAs) and other molecular signals between cells. In other species, serum exosome-derived miRNAs can serve as good biomarkers of diseases and different physiological states, including pregnancy status. We hypothesized that circulating exosome-derived miRNAs might be used to differentiate the pregnancy status as early as several days after insemination in pigs. To test this hypothesis, we randomly assigned pigs for artificial insemination with fertile or dead semen (control group). Serum samples were obtained from pregnant pigs on days 9, 12, and 15 after insemination and from non-pregnant pigs on days 0, 9, 12, 15 after insemination. Exosomes were isolated for RNA extraction. The exosomal RNA samples from pigs on day 9 of the estrus cycle and pregnancy were used for small-RNA sequencing. A total 321 miRNAs were identified in all samples. 28differentially abundant miRNAs were identified between the pregnant and control groups. miRNAs with |log2(fold change)|>2 from sequencing results were selected for validation by quantitative reverse-transcription-polymerase chain reaction (RT-qPCR) in larger samples. Finally two upregulated miRNAs (miR-92b-3p and miR-17-5p) in the pregnant groups (on days 9, 12 and 15 of pregnancy)were confirmed by RT-qPCR. In summary, we have successfully identified circulating exosomal miRNA profiles in the serum of pigs in early pregnancy. miR-92b-3p and miR-17-5p could be used as potential circulating biomarkers for early pregnancy diagnosis.